Role of 256 slice CT scan in pre and postoperative evaluation of congenital cardio-vascular anomalies: our experience at a tertiary care teaching hospital - Dashottar, Sunita; Singh, Ajay K.; Senger, K. P. S.; Debnath, Col J. (International Journal of Advances in Medicine, 2017)
Background: Ultrafast CT (UCT) scan plays an important role in the evaluation of congenital cardiovascular anomalies (CCVA). A major advantage of higher slice multi-detector CT (MDCT), is improved temporal as well as spatial resolution, that helps accurately to delineate complex cardiac and extra-cardiac anomalies with relative ease. Hence this study was aimed to highlight the utility of UCT in the evaluation of congenital cardiovascular anomalies in a large series of patients. Methods: All consecutive patients with suspected CCVA were evaluated by cardiac CT angiography (CCTA) on 256 slice CT scan in a multispecialty tertiary care teaching institute from June 2013 to December2015. Results: A total of 160 cases of CCVA were evaluated by CCTA. 50 patients had multiple anomalies. A total of 216 anomalies were diagnosed. Tetralogy of fallot (TOF) dominated the list of CCVAs (60, 28%) than the other abnormalities. Of them, 25 patients underwent Blalock Taussig (BT) shunt surgeries, 20 patients underwent total repair operation like Rastelli’s operation or augmentation of pulmonary arteries (PAs) while 15 patients were lost to follow up. Most of the patients diagnosed with CCVAs were managed successfully based on the imaging diagnosis of the cardiovascular anomaly. Conclusions: Ultrafast CT scans have immense role in the evaluation of various types of congenital cardiovascular anomalies. It is particularly helpful in the evaluation of extra-cardiac systemic and pulmonary arterial and venous system, postoperative complications, to see the status of shunts, stents and conduits.